Designing a Model for the Development of Millennial Farmer Human Resources in the Context of Sustainable Agriculture - Vilia Putri Sukmayahya; Solehudin; Nadeak, Banuara; Jajang S, Dede (Jurnal Sosial Humaniora, 2025)
This study aims to design a model for the development of millennial farmer human resources in the context of sustainable agriculture in Subang Regency, West Java. The phenomenon of aging farmers and the declining interest of the younger generation in the agricultural sector are the background of this research. Using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model approach, this study identifies the characteristics and needs of millennial farmers, designs a human resource development model, and evaluates its effectiveness. The results of the study show that millennial farmers have a high openness to innovation and modern agricultural technology, but the number is still limited. The developed model includes components of recruitment, training, mentoring, career development, resource access, and collaboration networks. The implementation of the model showed a significant increase in the interest of the younger generation in agriculture (200%), the adoption of modern agricultural technology (275%), and the application of sustainable agricultural practices (167%). The productivity and income of millennial farmers also increased by 50%. This research makes an important contribution to the development of millennial farmer human resources and supports sustainable agriculture, and highlights the importance of cross-sector collaboration and policies that support farmer regeneration.